TNF-α Gene Expression in Subcutaneous Adipose Tissue Associated with HOMA in Asian Indian Postmenopausal Women - Tiwari, S.; null; Paul, B. N.; Kumar, S.; Chandra, A.; Dhananjai, S.; Negi, M. P. S. (Hormone and Metabolic Research, 2014)
The present study determines the fat depot-specific expression of leptin and TNF-α and its association with biochemical parameters in postmenopausal women. A total of 108 postmenopausal women were recruited prospectively; 54 were with metabolic syndrome (cases) and 54 were without metabolic syndrome (controls). Leptin and TNF-α mRNA expression in visceral adipose tissue (VAT) and subcutaneous adipose tissue (SAT) were done by Real Time-RT PCR. In cases, the mean (±SD) serum estrogen was significantly lower (41.33±24.90 vs. 23.95±14.45, p<0.001) while leptin (12.85±4.51 vs. 10.34±3.89, p=0.002) and TNF-α (13.81±7.13 vs. 8.00±4.38, p<0.001) were significantly higher as compared to controls. Further, the mean relative VAT mRNA expression of both leptin (0.33±0.29 vs. 0.05±0.09, p<0.001) and TNF-α (0.32±0.31 vs. 0.13±0.09, p<0.001) and expression of SAT leptin (4.91±4.01 vs. 0.50±0.92, p<0.001) also lowered significantly in cases as compared to controls. Further, the relative VAT expression of both leptin (r=−0.32, p<0.001) and TNF-α (r=−0.23, p<0.01) showed significant and negative correlation with glucose; expression of SAT leptin showed significant and positive correlation with HDL (r=0.20, p<0.05) and serum estrogen (r=0.30, p<0.01) while negative correlation with glucose (r=−0.26, p<0.01) and serum TNF-α (r=−0.29, p<0.01); and expression of SAT TNF-α showed significant and positive correlation with insulin (r=0.21, p<0.05) and HOMA (r=0.20, p<0.05). In conclusion, the VAT and SAT leptin mRNA expressions may have a modulatory role in metabolic syndrome.
Keywords: adipokines; metabolic syndrome; adipose tissue; hyperinsulinemia; leptin; obesity; postmenopause